Elevated BCAA Suppresses the Development and Metastasis of Breast Cancer - Chi, Rui; Yao, Chengcheng; Chen, Si; Liu, Yunxia; He, Yanqi; Zhang, Jin; Ellies, Lesley G.; Wu, Xuefeng; Zhao, Qian; Zhou, Cixiang; Wang, Ying; Sun, Haipeng (Frontiers in Oncology, 2022)
Branched-chain amino acids (BCAAs) are the three essential amino acids including leucine, isoleucine, and valine. BCAA metabolism has been linked with the development of a variety of tumors. However, the impact of dietary BCAA intake on breast tumor progression and metastasis remains to be fully explored. Here, we unexpectedly find that the elevated BCAA, either in the genetic model or via increasing dietary intake in mice, suppresses the tumor growth and lung metastasis of breast cancer. The survival analysis show that BCAA catabolic gene expression is strongly associated with long-term oncological outcomes in patients with breast cancer. In Pp2cm knockout mice in which BCAAs accumulate due to the genetic defect of BCAA catabolism, the breast tumor growth is suppressed. Interestingly, while the cell proliferation and tumor vasculature remain unaffected, more cell death occurs in the tumor in Pp2cm knockout mice, accompanied with increased natural killer (NK) cells. Importantly, increasing BCAA dietary intake suppresses breast tumor growth in mice. On the other hand, there are fewer lung metastases from primary breast tumor in Pp2cm knockout mice and the high BCAA diet-fed mice, suggesting high BCAA also suppresses the lung metastasis of breast cancer. Furthermore, low BCAA diet promotes lung colonization of breast cancer cells in tail vein model. The migration and invasion abilities of breast cancer cells are impaired by high concentration of BCAA in culture medium. The suppressed tumor metastasis and cell migration/invasion abilities by elevated BCAA are accompanied with reduced N-cadherin expression. Together, these data show high BCAA suppresses both tumor growth and metastasis of breast cancer, demonstrating the potential benefits of increasing BCAA dietary intake in the treatment of breast cancer.